2009
DOI: 10.1007/s00265-009-0754-1
|View full text |Cite
|
Sign up to set email alerts
|

Movement signal choreography unaffected by receiver distance in the Australian Jacky lizard, Amphibolurus muricatus

Abstract: Theory explains the structure of animal signals in the context of the receiver sensory systems, the environment through which signals travel and their information content. The influence of signalling context on movementbased signalling strategies is becoming clearer. Building upon recent findings that demonstrated changing environmental plant motion conditions resulted in a change of signalling strategy by the Australian lizard Amphibolurus muricatus, we examined whether receiver distance also influences signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…These adjustments serve to vary the active space of the signal and have been shown to vary in the movement-based displays of other taxa (How et al 2008 ). However, Peters and Allen ( 2009 ) demonstrated that A. muricatus do not adjust tail displays in this way in response to receiver distances. Amplitude variability was a feature of each tail flicking sequence, but amplitudes were (almost) always greater than push-ups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These adjustments serve to vary the active space of the signal and have been shown to vary in the movement-based displays of other taxa (How et al 2008 ). However, Peters and Allen ( 2009 ) demonstrated that A. muricatus do not adjust tail displays in this way in response to receiver distances. Amplitude variability was a feature of each tail flicking sequence, but amplitudes were (almost) always greater than push-ups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ord & Stamps (2008) demonstrated that A. gundlachi is more likely to use high-amplitude motion patterns at the beginning of their display when the receiver is several metres away, particularly in viewing conditions where detection is more difficult. On the other hand, in the only direct experimental test of this idea on a lizard, Peters & Allen (2009) found that Jacky lizards (A. muricatus) make no change in threat display amplitude based on the distance to an intruder. Clearly, the influence of receiver distance on display amplitude merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…The animated lizard was scaled to be life-sized as viewed from three meters. Both the subject scaling and distance was selected based on the appropriate measures for scaling that continued to elicit responses from typical distances between individuals in the wild (Peters, 2013;Peters & Allen, 2009;Peters et al, 2008). Each type of background was placed in the backdrop of each of the three display animation sequences (see Phases 1 and 2 for background descriptions).…”
Section: Animation Sequencesmentioning
confidence: 99%